Noun Composition in Narrative Passage - Sulistyowati, Heny; Mahatmaharti, Agung Kesna; Lubis, Tasnim (TALENTA Publisher, 2022)
The morphology process in forming the words needs a formation component or element of words, an affixation process, a reduplication process, and a composition process. Composition is combining two or more words that create a new meaning. The problem focus of this research was basic composition in narrative passages with basic forms of nouns and adjectives. The method used in this research was the descriptive qualitative method. The researcher used this descriptive qualitative method to describe the basic composition form and affixed composition objectively. The data source used in this research was narrative passage research on the origins of the Jombang Regency. Data were in the form of Indonesian language composition. The research found categories of basic noun composition forms such as (N+N) and (N+Adj). The form of the adjective basic composition category found is (Adj + V) and (Adj + Adj).